Treatment of Mooren's ulcer with cyclosporin A: report of three cases. Issue 1 (January 1987) - Hill, J C; Potter, P
Abstract : Three patients with severe, bilateral, progressive Mooren's ulcers, unresponsive to medical and surgical therapy, were treated with cyclosporin A. All three responded rapidly to the drug and there has been no recurrence of the Mooren's ulcers since (average follow-up 14 months). Peripheral blood T lymphocyte subsets were estimated prior to and during treatment. No significant abnormalities were found initially. Suppressor cells increased on treatment, and a corresponding drop of the helper/suppressor cell ratio occurred in two patients.